The Birds of Wapusk National Park - Rockwell, Robert; Abraham, Kenneth F.; Witte, Christopher; Matulonis, Paul; Usai, Michael; Larsen, Drake; Cooke, Fred; Pollak, Diana; Jefferies, Robert L. (Parks Canada, 2009)
This occasional paper was published by Wapusk National Park and Parks Canada. It was co-written, among others, by Dr. F. Cooke and Dr. R.L. Jefferies.